Occurrence of small to moderate magnitude earthquakes in Kachchh intraplate zone: A special emphasis to the 2020 Bhachau earthquake. Issue 7 (1st June 2022) - Choudhury, Pallabee; Kamra, Charu; Kumar, Santosh; Singha Roy, Ketan; Madhusudhana Rao, K.; Chopra, Sumer; Ravi Kumar, M.
Highlights: A magnitude ∼5 earthquake occurred in the South Wagad Fault system after 19 years. The epicentre of the Mw 5.3 earthquake is close to the 2001 Mw 7.7 Bhuj earthquake. Occurrence of Mw 5.3 earthquake has given impetus to constrain the seismotectonics. The Mw 5.3 earthquake triggered two M > 4 earthquakes on a nearby fault within 2 days. The Mw 5.3 earthquake and the subsequent ones occurred in the SWF double fault zone. Intermediate stress is accumulated in the SWF double fault zone. Some new insights are obtained on active faults and their spatial diversity. Abstract: Since the 2001 Mw 7.7 Bhuj earthquake in Gujarat, western India, a number of small-to-moderate earthquakes have occurred to the east of the Bhuj rupture, near the town of Bhachau. In this paper, we present an overview of seismic monitoring in the region, and analysis of a Mw 5.3 earthquake that occurred near Bhachau on 14 June 2020. Moment tensor analysis of regional broadband data reveals a reverse mechanism with a small strike-slip component, generally similar to that of the 2001 Bhuj earthquake. A total of 20 aftershocks with magnitudes ranging from 2.0 to 4.6 were recorded within the first 10 days of the sequence. After that, this region recorded 129 tremors of magnitude 2.0–4.2 until June 2021. We conclude that this sequence occurred on the South Wagad fault (SWF)-Kachchh Mainland fault (KMF) system, a complex zone comprising many separate mapped faults. A recent analysis of Global Positioning System (GPS) data reveals that the area is under broad compressive stress, with a maximum strain of 5 nano-strain/year. The occurrence of the 2020 Bhachau earthquake underscores concerns for continuing seismic hazard in the region.